A Study on the Presence of Inter-Area Oscillation Mode in Bangladesh Power System Network - Jan-E-Alam, Md (Journal of Electrical Engineering, 2011)
Inter-Area modes of oscillation are of significant concern in interconnected system operation, considering the fact that these oscillations involve units from different areas of a power system and hence may result in a higher oscillation in the tie-line by adding up effects from each of the units participating. Research has been going on in this area ever since the growth of interconnection among electric utilities, to fully understand, monitor and control this phenomenon. Bangladesh Power System Network (BPSN), being an interconnected system consisting of greater Eastern and Western Grid, might also be vulnerable to the effects of interarea modes and if not identified and studied, might lead to unexpected contingencies. In this paper, a study on the presence of inter-area mode in BPSN has been performed. A detailed model of BPSN has been used, represented by a 166 Bus and 27 Generator system. Index Terms: Bangladesh Power System Network; interconnected system; grid; inter-area mode. J. Elec. Engg., Instn. Engrs., Bangladesh, 36(II), December 2009: 16-21